2016
DOI: 10.1590/0100-69912016003003
|View full text |Cite
|
Sign up to set email alerts
|

The history of the parathyroid surgery

Abstract: Rev. Col. Bras. Cir. 2016; 43(3): INTRODUCTION Hyperparathyroidism is a condition in whichthere is an abnormal increase in the levels of parathyroid hormone (PTH), responsible for regulating the level of blood calcium and phosphate. The most common cause of hyperparathyroidism, seen in about 80% of cases, is the primary gland dysfunction due to an adenoma. Multiple adenomas or hyperplasia of the parathyroid glands are diagnosed in the remaining patients. Rarely the cause of hyperparathyroidism is a result of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 36 publications
0
12
0
5
Order By: Relevance
“…27 Indeed, this was first evident when patients who underwent TT by Theodor Kocher, using his principles of bloodless surgery, had a lesser incidence of postoperative hypocalcemia as compared with those operated by Billroth. 28 However, a recent study found that patients operated by surgical trainees had complications that were comparable to patients operated on by consultant surgeons.…”
Section: Risk Factorsmentioning
confidence: 98%
“…27 Indeed, this was first evident when patients who underwent TT by Theodor Kocher, using his principles of bloodless surgery, had a lesser incidence of postoperative hypocalcemia as compared with those operated by Billroth. 28 However, a recent study found that patients operated by surgical trainees had complications that were comparable to patients operated on by consultant surgeons.…”
Section: Risk Factorsmentioning
confidence: 98%
“…At the same time, the first parathyroid tumors and adenomas were described, and the premier autotransplantations were rehearsed. 14 By 1920’s, knowledge on the parathyroid glands had entered a new era. The parathyroid hormone was isolated in 1924.…”
Section: Churchill’s Work On Parathyroid Surgerymentioning
confidence: 99%
“…Parathyroid surgeries were often prolonged, tedious, and unsuccessful operations in the past. However, the advances in technology and the adaptation of minimally invasive techniques now allows performing surgeries with very short hospital stay, less pain, lower cost, and minimal scars . In‐hospital mortality rates after PTX for SHPT steadily declined between 2002 and 2011 and were <1% in recent years …”
Section: Surgical Management Of Shptmentioning
confidence: 99%